2012
DOI: 10.1176/appi.neuropsych.11090216
|View full text |Cite
|
Sign up to set email alerts
|

Agomelatine in Depressive Disorders: Its Novel Mechanisms of Action

Abstract: Disruptions in sleep and sleep-wake cycle regulation have been identified as one of the main causes for the pathophysiology of depressive disorders. The search has been on for the identification of an ideal antidepressant that could improve both sleep disturbances and depressive symptomatology. Melatonin, the major hormone of the pineal gland, has been shown to improve sleep and is involved in the regulation of the sleep-wake cycle. Identification of high concentrations of MT1 and MT2 melatonergic receptors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 175 publications
1
29
0
2
Order By: Relevance
“…[33] The effect of agomelatine on inflammation was studied by Molteni et al [34] Pro-inflammatory cytokines were found to be reduced in rats treated with agomelatine, a finding similar to that of the present study. The authors reported that agomelatine modified the expression of enzymes involved in the kynurenine pathway.…”
Section: Discussionsupporting
confidence: 88%
“…[33] The effect of agomelatine on inflammation was studied by Molteni et al [34] Pro-inflammatory cytokines were found to be reduced in rats treated with agomelatine, a finding similar to that of the present study. The authors reported that agomelatine modified the expression of enzymes involved in the kynurenine pathway.…”
Section: Discussionsupporting
confidence: 88%
“…High concentrations of melatonin in an exposure-timing-dependent manner (104) and at physiologic concentration, particularly through MT 1 receptors in the SVZ, have a modulatory effect on neural stem cell proliferation and differentiation (86). Recent studies have identified functions in neurogenesis for MT 1 and MT 2 agonists, including agomelatine (105,106), buspirone in combination with melatonin in major depressive disorder (107), and Nacetylserotonin, an intermediate of melatonin synthesis (108). Some evidence shows that a combination of melatonin and physical exercise enhances neurogenesis and neural survival (109) and some melatonin-receptor agonists promote proliferation in the dentate gyrus (110).…”
Section: Central and Peripheral Nscs Agingmentioning
confidence: 99%
“…Некоторые исследования показали положи-тельные эффекты мелатонина для лечения нарушений сна [46][47][48], но применение мелатонина ограничено его низкой биодоступностью. На сегодняшний день аго-мелатин имеют самую большую клиническую базу из всех синтетических агонистов MT1 и MT2 мелатони-новых рецепторов.…”
Section: Antidepressants In Ischemic Heart Diseaseunclassified